(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To exemplify the stress, distress, and coping assessment perceived by patients with hard-to-heal wounds (HHW) receiving treatment in a Stomatherapy outpatient clinic. Methods: Observational, prospective secondary study involved 10 adult patients with HHW, who were followed over two to six consultations. The following tools were used: sociodemographic and clinical data form; Brief Pain Inventory (sensitivity - BPI-S and interference - BPI-I); Bates-Jensen Wound Assessment Tool (BWAT); Perceived Stress Scale (PSS), which included measures of coping and distress with data expressed as means. Results: Patients primarily had HHW located on the lower extremities, with a duration of 21.2 months; BWAT score was 23.7; BPI-S was 4; and BPI-I was 3.2. Stress was characterized by a total PSS score of 28.5 points, with a distress score of 16.4 and a coping score of 16. In the final consultation, there was a decrease of 4.3 points in BWAT; 0.8 points in BPI-S; and 7.6 points in PSS, with a 5.3 point reduction in distress. The BPI-I increased by 0.7, and coping improved by 2.2. Conclusion: The wound seems to interfere with the level of perceived stress, i.e. the patient’s biopsychosocial dimension. Coping stands out as a determining factor in the perception of stress, and a multidisciplinary approach is essential for its management and assessment of distress.